THE DECLINE OF PROTEOSTASIS IN AGING. (11th November 2018) - Cuervo, A
Abstract: The components of the proteostasis networks, chaperones and proteolytic systems, are responsible for the maintenance of a healthy and functional proteome. Malfunctioning of the proteasome and autophagy, the two main proteolytic systems that contribute to proteostasis, occurs with age. In this session, we will discuss current efforts to adjust the activity of the proteasome (Dr. Goldberg and Dr. Finley) and autophagy systems (Dr. Cuervo and Dr. Hansen) in aging that originate from novel insights on the regulation of these systems. Dr. Goldberg will describe a novel proteasome regulatory axis (cAMP/protein kinase A) and their efforts to enhance proteasome activity by regulating intracellular cAMP levels. Dr. Finley will present different strategies to upregulate proteasome activity based on inhibition of deubiquitinating enzymes. Dr. Cuervo will share their efforts to restore the activity of a selective form of autophagy known to decline in aging using both genetic and chemical approaches. Dr. Hansen will discuss novel molecular mechanisms that contribute to regulation of autophagy in stress and aging.